Biopolymers in Nutraceuticals and Functional Foods 2022
DOI: 10.1039/9781839168048-00488
|View full text |Cite
|
Sign up to set email alerts
|

Food-based Polymers for Encapsulation and Delivery of Bioactive Compounds

Abstract: Nutrient delivery systems are a new and fast-growing topic that covers various disciplines and has various applications in the food industry. This chapter seeks to bring current understanding on food-grade biopolymer-based approaches to developing nutrient compound delivery facilities up to date. The development of carriers derived from food biopolymers is a particular focus of research. In addition, several types of specifically updated nutrition delivery systems and their applications are reviewed. The diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 254 publications
0
4
0
Order By: Relevance
“…By encapsulating CUR in SLNs, the compound can be targeted to the brain, which can more effectively cross the BBB and interact with the affected cells in AD. 69 Preclinical research has indicated that CUR-containing SLNs can decrease the development of Aβ plaques, a characteristic of AD. They also appear to have neuroprotective effects and improve cognitive function in animal models of the disease.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…By encapsulating CUR in SLNs, the compound can be targeted to the brain, which can more effectively cross the BBB and interact with the affected cells in AD. 69 Preclinical research has indicated that CUR-containing SLNs can decrease the development of Aβ plaques, a characteristic of AD. They also appear to have neuroprotective effects and improve cognitive function in animal models of the disease.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…SLNs are small, spherical structures made of lipids that can encase and deliver drugs to specific body areas. By encapsulating CUR in SLNs, the compound can be targeted to the brain, which can more effectively cross the BBB and interact with the affected cells in AD …”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…The selection of the matrix is crucial for the development of intelligent pH-sensitive indicators. The functional packaging nano ber mats must possess sensitivity to a broad spectrum of pH values and exhibit quick reactivity towards gaseous amines emitted by contaminated food (Ekrami et al 2022d). Electrospinning is an innovative nanotechnology method used to encapsulate natural colours.…”
Section: Al 2023)mentioning
confidence: 99%
“…Bioactive molecules, which have the capability to interact with components of living tissue to produce a physiological effect, were a specific area of concern. While many bioactive compounds are present in conventional foods, some bioactive molecules are expected to be new to food production or used in novel ways for the production of CM, such as small molecules, hormones, or growth factors [27]. Participants noted that while many are naturally present in conventional meat and seafood, the majority of these inputs have no previous use as additives in food production and therefore do not have available toxicology information or existing risk assessments.…”
Section: Bioactive Moleculesmentioning
confidence: 99%